A Combined Balance and Plyometric Training Approach: Effects on Physical Performance Parameters in Youth Male Handball Players: A Randomized Controlled Trial - Ghaith Aloui; Wissem Dhahbi; Halil İbrahim Ceylan and Valentina Stefanica and Abdulla Alneama and Maroua Mami and Lawrence Hayes D and Rаul-Ioаn Munteаn and Souhail Hermassi (Revista de Psicología del Deporte (Journal of Sport Psychology), 2025)
The physical quality of young male handball players is one of the essential factors that influence team performance. Balance and plyometric training refers to the work of muscle groups related to stabilization located at the meeting of the base of the trunk, spine, pelvis and lower extremities of the human bodyThirty male handball players (age: 16.6±0.5 years) were randomly allocated to either an experi-mental group (n=15) performing combined postural control and plyometric training twice weekly in addition to standard handball training, or a control group (n=15) maintaining regular training alone. Pre- and post-intervention assessments included vertical jump performance (squat jump, countermovement jump), horizontal jump ability (standing long jump), linear sprint speed (5m, 20m), change-of-direction capac-ity (modified T-test, Illinois modified test), repeated change-of-direction ability, and postural control (Stork Balance test, Y-Balance test). The experimental group demonstrated significantly greater improvements compared to controls across multi-ple performance domains. Specifically, superior adaptations were observed in the squat jump (p<0.05), countermovement jump (p<0.01), and standing long jump (p<0.05) performance. Sprint capabilities showed enhanced development in both 5m (p<0.05) performance. Sprint capabilities showed enhanced development in both 5m (p<0.05; d=0.56 [moderate]) and 20m (p<0.05) times. Change-of-direction ability improved sub-stantially in both single-effort (T-half test: p<0.01; Illinois-MT: p<0.01; d=0.85 [large]) and repeated-effort contexts (p=0.05). Dynamic balance measures showed consistent improvements across all planes of movement (p<0.05). Conclusion: Implementing combined postural con-trol and plyometric training twice weekly during the competitive season effectively enhanced multiple aspects of physical performance in youth handball players. The moderate to large effect sizes observed across performance measures suggest this training approach represents an effective strategy for developing athletic capabilities in this population.